2007
DOI: 10.1080/17482960600982447
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in disease onset and progression of a rat model of ALS

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease causing the progressive loss of brain and spinal cord motor neurons. The exact etiology of ALS is still uncertain, but males have consistently been shown to be at a higher risk for the disease than females. Recently, transgenic rats overexpressing mutant forms of the human SOD1 (hSOD1) gene have been established as a valuable disease model of ALS. Here we show that sexual dimorphism in disease onset is also observed in hSOD1G93A transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 22 publications
8
54
0
Order By: Relevance
“…For example, studies with untreated mutant SOD1 mice [31] and rats [52], including results from the present study, demonstrate that disease onset and overall survival occur earlier on average in males. In response to an exercise regimen therapy, delayed disease onset and survival was noted in only female mice [55], while AAV2 IGF-1 promoted benefit selectively in males in the present study.…”
Section: Sex-specific Effectssupporting
confidence: 54%
See 1 more Smart Citation
“…For example, studies with untreated mutant SOD1 mice [31] and rats [52], including results from the present study, demonstrate that disease onset and overall survival occur earlier on average in males. In response to an exercise regimen therapy, delayed disease onset and survival was noted in only female mice [55], while AAV2 IGF-1 promoted benefit selectively in males in the present study.…”
Section: Sex-specific Effectssupporting
confidence: 54%
“…Sex-specific differences in disease onset and progression [31,40,52,55] and response to therapeutic interventions [16] have been noted in CNS disorders, including ALS. For example, studies with untreated mutant SOD1 mice [31] and rats [52], including results from the present study, demonstrate that disease onset and overall survival occur earlier on average in males.…”
Section: Sex-specific Effectsmentioning
confidence: 99%
“…G93A rats, with males having an earlier disease onset than females (24). In our hands, male rats also demonstrated a more consistent disease phenotype (data not shown), as a result of which we only examined male animals.…”
Section: Animalsmentioning
confidence: 54%
“…Glial-derived neurotrophic factor dent models of ALS that mimic human disease with comparable progressive motor dysfunction and respira-(GDNF)-producing human cortical neural precursors spinally grafted to G93A rats significantly improved tory failure (17,23). motoneuron survival (30). However, cell graft survival the ventral horn (distance from the dorsal surface of the spinal cord at L3 level: 1.1-1.2 mm) (16).…”
Section: Introductionmentioning
confidence: 99%
“…Derivation of the Spinal hSSCs (30) and Klein et al (19) both reported poor graft survival with cyclosporin A immunosuppression after spiHuman SSCs were prepared from the cervical-upper thoracic region of spinal cord tissue obtained from a sinnal grafting of human neural progenitors in the G93A rat. Other studies, while reporting positive functional gle 8-week human fetus after an elective abortion.…”
Section: Introductionmentioning
confidence: 99%